Quality indicators of pharmacists' services in community pharmacies in Paraná State, Brazil - Edson Hipólito Júnior; Gerusa Clazer Halila; Walleri Christini Torelli Reis; Matheus Murmel Guimarães; Laís Danciguer Guanaes; Roberto Pontarolo; Cassyano Januário Correr (Universidade de São Paulo, 2017)
ABSTRACT Pharmacists and their pharmacies have been evolving in their roles as health promoters in Brazil. Some examples are the recent legislation reaffirming the role of Brazilian pharmacies as health institutions, rather than having only a commercial profile, giving greater clarity to pharmacists about their roles as health care providers. This evolution came with the recognition that is already seen in other developed countries, confirming the need for the pharmacist as a health promoter, and not simply a dispenser of drugs in society. This study has obtained the profile and activities of community pharmacists, as well as the quality indicators of private community pharmacies throughout the State of Paraná through the application of an online survey sent to pharmacists in the state. Out of all pharmacists surveyed, 533 were part of the final analysis, being the pharmacists to complete the survey in full. Participants were mostly female (69.4%) and were, on average, 35.2 ± 9.2 years old. Of these, 60% worked in pharmacy chains and just 37% of all pharmacist respondents were issuing the Declaration of Pharmaceutical Services. The current study showed that many pharmaceutical services are not adopted by pharmacies as these services bring no significant financial reward. Regarding the structure, the Paraná State showed that pharmacies present a good overall structure. The kind of pharmacy (chain or independent) influenced the pharmaceutical services provided and the available structure, where the independent pharmacies provide a wider range of services and have better structure. This study was able to identify the profile and behaviors of pharmacists and also the quality indicators of pharmacies in Paraná State.